2022
DOI: 10.1038/s41467-022-35547-0
|View full text |Cite
|
Sign up to set email alerts
|

Muscle 4EBP1 activation modifies the structure and function of the neuromuscular junction in mice

Abstract: Dysregulation of mTOR complex 1 (mTORC1) activity drives neuromuscular junction (NMJ) structural instability during aging; however, downstream targets mediating this effect have not been elucidated. Here, we investigate the roles of two mTORC1 phosphorylation targets for mRNA translation, ribosome protein S6 kinase 1 (S6K1) and eukaryotic translation initiation factor 4E-binding protein 1 (4EBP1), in regulating NMJ structural instability induced by aging and sustained mTORC1 activation. While myofiber-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 37 publications
1
12
1
Order By: Relevance
“…Previous reports identify the mTORC1 signaling pathway as a key regulator of NMJ physiology: mTORC1 is activated in response to denervation and it drives NMJ structural instability during aging 11, 30, 49, 50 . To assess potential functional interactions between SOCE and mTORC1, we first investigated whether mTORC1 modulation affects SOCE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports identify the mTORC1 signaling pathway as a key regulator of NMJ physiology: mTORC1 is activated in response to denervation and it drives NMJ structural instability during aging 11, 30, 49, 50 . To assess potential functional interactions between SOCE and mTORC1, we first investigated whether mTORC1 modulation affects SOCE.…”
Section: Resultsmentioning
confidence: 99%
“…While the mTORC1 pathway has been shown to play a key role in NMJ maintenance and the muscle response to denervation, downstream targets mediating this effect are not well understood 11, 30, 50, 72 . We identify that constant mTORC1 activation in TSCmKO mice results in a strong increase in SOCE capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, loss of synaptic myonuclei occurs with aging and corresponds with NMJ structural and functional defects. A recent study revealed that increasing synaptic myonuclear number by muscle activation of 4EBP1, a mRNA translation regulator, led to increased acetylcholine receptor subunit expression and neurotransmission in aged mice (Ang et al, 2022). Postsynaptic BMP signaling could also be a good target in sarcopenia, an aging-related process of muscle deterioration and other conditions that implicate NMJ activity in their initiation and/or disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…The mTOR signaling pathway is well described to be involved in protein synthesis, muscle hypertrophy and growth ( Bodine et al, 2001 ; Schiaffino et al, 2021 ). However, sustained activation of mTORC1 can lead to pulmonary fibrosis ( Gui et al, 2015 ) and drive neuromuscular junction structural alterations, resulting in myofiber denervation ( Ang et al, 2022 ), muscle atrophy, loss of muscle mass ( Tang et al, 2014 , 2019 ) and late-onset myopathy by increasing the expression of the E3 ubiquitin ligases atrogin1 and MuRF1 and impairing autophagy ( Castets et al, 2013 ). Inhibition of mTORC1 by rapamycin improves muscle pathology in the fukutin-deficient mouse model of dystroglycanopathy ( Foltz et al, 2016 ) and the mdx mouse model of Duchenne muscular dystrophy ( Eghtesad et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%